O clickbait no ciberjornalismo português e brasileiro: o caso brasileiro - Pedro, Margarete Vieira (2019)
The paper aims to analyze the incidence of clickbait in Portuguese and Brazilian online journalism. It is part of an activity carried out jointly by Brazilian and Portuguese researchers, in which each group carried out the verification in the Web and Facebook pages of 18 general information vehicles of such countries, each having national coverage, as well as its own production and frequent updates. This article presents the results found in the Brazilian sample that shows a high clickbait index, of 54.4%, when crosschecking the general data. On the other hand, the values are reduced when we look at the 32 indicators individually, in which only three had rates above 10%.